THE EFFECT OF MACRO-ECONOMIC INDICATORS ON SHARE PRICES IN THE CONSTRUCTION SUB-SECTOR AND BUILDING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2013-2018 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The role of the construction and building sector as a conducive national economic driver is influenced by many factors, including through the support of government regulations, sectoral policies, good governance, business structure, the composition of the size of the market supply and demand and economic growth. The purpose of this study is to determine the effect of exchange rates, inflation, world oil prices, and exchange rates on stock prices in the construction and building sub-sector on the Indonesia Stock Exchange 2013-2018 period. The population in this study is the construction and building sub-sector companies in the Indonesia Stock Exchange, amounting to 16 companies with a sample of 9 companies selected using purposive sampling. The type of data used in this study is secondary data in the form of comparisons, world oil prices, and exchange rates. Methods of data analysis using panel data regression method using a random effect model (RE). The results showed that inflation and world oil prices have an effect on stock prices. Meanwhile, the exchange rate does not affect the stock price.